One new species of the genus Kuzicus (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China - Han, Li; Shi, Fu-Ming (Zootaxa, 2014)
One new species is described, i.e. Kuzicus (Kuzicus) compressus Han & Shi sp. nov. The type species is preserved in the Museum of Hebei University.